Autonomous Observations in Antarctica with AMICA - Gianluca Di Rico; Maurizio Ragni; Mauro Dolci; Oscar Straniero; Angelo Valentini; Gaetano Valentini; Amico Di Cianno; Croce Giuliani; Demetrio Magrin; Carlotta Bonoli; Favio Bortoletto; Maurizio D'Alessandro; et al. (Advances in Astronomy)
The Antarctic Multiband Infrared Camera (AMICA) is a double channel camera operating in the 2–28 𝜇m infrared domain (KLMNQ bands) that will allow to characterize and exploit the exceptional advantages for Astronomy, expected from Dome C in Antarctica. The development of the camera control system is at its final stage. After the investigation of appropriate solutions against the critical environment, a reliable instrumentation has been developed. It is currently being integrated and tested to ensure the correct execution of automatic operations. Once it will be mounted on the International Robotic Antarctic Infrared Telescope (IRAIT), AMICA and its equipment will contribute to the accomplishment of a fully autonomous observatory.